A new species of the genus Eugoa Walker, 1858 (Lepidoptera, Erebidae, Arctiinae) from Cambodia - Bayarsaikhan, Ulziijargal; Ko, Jae˗ho; Bae, Yang˗seop (Zootaxa, 2019)
A new Lithosiini species, Eugoa leucomelaena n. sp. is described from Cambodia. A diagnostic comparison is made with Eugoa arida van Eecke, 1920, E. aridoides Holloway, 2001, E. grandipuncta Bucsek, 2008 and E. gracilisa Bucsek, 2008. Moreover, adult, male and female genitalia of E. arida van Eecke are illustrated for the first time. Illustration of adults, male and female genitalia of the new and closely allied species are presented.